Banker to the third world : US portfolio investment in Latin America, 1900-1986 - Stallings, Barbara (University of California Press, 2018)
By the end of 1985, Latin Americans owed their foreign creditors 368 billion. That was nearly 1,000 for every man, woman, and child between the Rio Grande and Tierra del Fuego. The debt represented more than half of the region's gross domestic product, and interest payments alone consumed 36 percent of export revenues. If profits are added to interest, and the total compared to new capital inflows, the drama of the situation becomes clear: a real resource tran.
Originally published in 1987.
Keywords: Investments, American -- Latin America -- History.; Loans, American -- Latin America -- History.; SOCIAL SCIENCE / Anthropology / Cultural & Social; Investments, American; Loans, American; Latin America; History